Stationary flow simulation model of the Ticlio hydrogeological system - Acuña Azarte, Magally (2008)
In the present work, the simulation model of groundwater flow in a stationary regime has been elaborated in the area of ​​the Ticlio mining unit over 300 hectares of surface and 4814 meters of altitude. Geologically, the unit is made up of karst aquifers and fissured and clastic aquitards, which store and carry water. The main source of recharge of the aquifers are the precipitations that occur during the rainy periods and the melting of the glaciers, which are stored in the San Nicolás and Santa Catalina lagoons, constituting these as the recharge sources of the mentioned aquifers during the periods of low water. The analytically estimated hydraulic conductivity and hydraulic transmissivity are 0.068 m / d and 6.48 m2 / d respectively, values ​​that must be corroborated by hydraulic tests to be carried out in wells or piezometers. The balance obtained with the aquifer simulation model is known that the drainage flow is 31.78 l / s, a value very close to the observed flow (30.20 l / s).